Can combining judgment decomposition and notetaking improve group auditors' sensitivity to qualitative risk? - Backof, Ann G.; Christensen, Brant E.; Glover, Steven M.; Schmidt, Jaime J. (Contemporary Accounting Research, 2025)
Abstract In this study, we leverage judgment decomposition and information acquisition theories to develop and test an intervention to improve group auditors' identification of and response to component‐level qualitative risk. Improving group auditors' response to qualitative risk is important because (1) group audits are prevalent today and require multiple qualitative risk assessments, (2) auditors have historically overlooked qualitative risks, and (3) prior interventions have failed to improve auditors' response to qualitative risk. In an experiment with 88 audit partners and managers, we find that a hybrid risk assessment approach that combines elements of judgment decomposition and notetaking improves auditors' group audit planning decisions. Specifically, auditors utilizing our hybrid approach are better able to identify and respond to component‐level qualitative risks than auditors who use a holistic approach. Importantly, the improvement in qualitative risk response does not come at the expense of auditors' response to quantitative risk.